Increased Sensitivity of Focused Cardiac Ultrasound for Pulmonary Embolism in Emergency Department Patients With Abnormal Vital Signs. (27th September 2019) - Daley, James I.; Dwyer, Kristin H.; Grunwald, Zachary; Shaw, Daniel L.; Stone, Michael B.; Schick, Alexandra; Vrablik, Michael; Kennedy Hall, M.; Hall, Jane; Liteplo, Andrew S.; Haney, Rachel M.; Hun, Nancy; et al.
Abstract: Background: Focused cardiac ultrasound (FOCUS) is insensitive for pulmonary embolism (PE). Theoretically, when a clot is large enough to cause vital sign abnormalities, it is more likely to show signs of right ventricular dysfunction on FOCUS, although this has not been well quantified. A rapid bedside test that could quickly and reliably exclude PE in patients with abnormal vital signs could be of high utility in emergency department (ED) patients. We hypothesized that in patients with tachycardia or hypotension, the sensitivity of FOCUS for PE would increase substantially. Methods: We performed a prospective observational multicenter cohort study involving a convenience sample of patients from six urban academic EDs. Patients suspected to have PE with tachycardia (heart rate [HR] ≥ 100 beats/min) or hypotension (systolic blood pressure [sBP] < 90 mm Hg) underwent FOCUS before computed tomography angiography (CTA). FOCUS included assessment for right ventricular dilation, McConnell's sign, septal flattening, tricuspid regurgitation, and tricuspid annular plane systolic excursion. If any of these were abnormal, FOCUS was considered positive, while if all were normal, FOCUS was considered negative. We a priori planned a subgroup analysis of all patients with a HR ≥ 110 beats/min (regardless of their sBP). We then determined the diagnostic test characteristics of FOCUS for PE in the entire patient population and in the predefined subgroup, based on CTA as the criterion standard. Inter‐rater reliability of FOCUS was determined by blinded review of images by an emergency physician with fellowship training in ultrasound. Results: A total of 143 subjects were assessed for enrollment and 136 were enrolled; four were excluded because they were non–English‐speaking and three because of inability to obtain any FOCUS windows. The mean (±SD) age of enrolled subjects was 56 (±7) years, mean (±SD) HR was 114 (±12) beats/min, and 37 (27.2%) subjects were diagnosed with PE on CTA. In all subjects, FOCUS was 92% (95% confidence interval [CI] = 78% to 98%) sensitive and 64% specific (95% CI = 53% to 73%) for PE. In the subgroup of 98 subjects with a HR ≥ 110 beats/min, FOCUS was 100% sensitive (95% CI = 88% to 100%) and 63% specific (95% CI = 51% to 74%) for PE. There was substantial interobserver agreement for FOCUS (κ = 1.0, 95% CI = 0.31 to 1.0). Conclusions: A negative FOCUS examination may significantly lower the likelihood of the diagnosis of PE in most patients who are suspected of PE and have abnormal vital signs. This was especially true in those patients with a HR ≥ 110 beats/min. Our results suggest that FOCUS can be an important tool in the initial evaluation of ED patients with suspected PE and abnormal vital signs.